PENGARUH KOMBINASI PENYUNTIKAN OVAPRIM DAN PROSTAGLANDIN F 2 α (PGF 2 α) TERHADAP VOLUME SEMEN DAN KUALITAS SPERMATOZOA IKAN TAMBAKAN (Helostama temmincki CV) - Sukendi, Sukendi; Putra, Ridwan Manda; Yurisman, Yurisman; Asiah, Nur (Fakultas Perikanan dan Kelautan Universitas Riau, 2011)
This research was aimed to know the effect of the best ovaprim andprostaglandin F2 α injection combination toward semen volume and spermatozoaquality of fish tambakan (Helostama temmincki CV). The result of this researchdemonstrated that the best injection combination was 50 % ovaprim + 50 % PGF2 (0,250 ml ovaprim + 1500 g PGF2  / kg of body), with a semen volume 1,10 ml,spermatozoa concentration 24.27x 10 9/ml, spermatozoa viability 87,23 % andspermatozoa motility 82,27 %)